FAKTOR-FAKTOR YANG MEMPENGARUHI TAX AVOIDANCE PADA PERUSAHAAN MANUFAKTUR DI INDONESIA - Tia Oktavia Puspitasari; Fung Njit Tjhai (E-Jurnal Akuntansi TSM, 2022)
The purpose of this research is to examine the effect of independent variables: firm size, firm age, independent board of commissioners, audit committee, sales growth, leverage, KAP size (audit quality) and profitability on the dependent variable: tax avoidance. The population of this research consisted of manufacturing companies listed on the Indonesia Stock Exchange during 2018 to 2020. The sample of this research used a purposive sampling method, where the sample that met the sampling criteria in this research only 189 data from 63 manufacturing companies listed on the Indonesia Stock Exchange during 2018 to 2020. This research used multiple regression model to examine the effect of each variable on tax avoidance. Multiple regression results indicates that sales growth and profitability have an influence on tax avoidance. However firm size, firm age, independent board of commissioners, audit committee, leverage and KAP size have no influence on tax avoidance.